Analysis, selection and implementation of the turbine of a turbocharger for its coupling in the OTEC-CC-MX-1kWe prototype plant - Amaro Rosas, Daniel Alejandro (2022)
It is proposed to implement a turbocharger turbine to the OTEC plant prototype to generate 1 kWe. The radius was defined as a physical parameter for the turbocharger selection, the type of coupling was selected, tests were carried out on the turbine using an air compressor, obtaining a maximum of 3400 rpm, generating 1255,2 We, according to data from supplier, proving that coupling the turbine of a turbocharger is technically feasible.